A global-level assessment of gulls (Larus spp.) as bioindicators of trace elements in coastal ecosystems - Bahamonde, Paulina; Espejo, Winfred; Celis, José; Montes, Isis-Yelena; Barra, Ricardo O. (My University, 2023)
ABSTRACT. Anthropogenic activities and the demand for trace elements have risen, causing an increase in their environmental levels, which could affect biota. High levels of trace elements in living beings have been associated with toxicity, metabolic disorders, oxidative stress, and cancer. Seabirds, such as gulls, have been used as bioindicators of environmental pollution caused by anthropogenic sources. Gulls are widely distributed worldwide, usually occupying high trophic levels, and living close to humans. Among gulls, Larus spp. are omnivorous, predominantly carnivorous, nest on the ground, and capture live food or steal it opportunistically. The present work summarizes the data of trace elements found in eggs, feathers, blood, and feces, among other internal tissues, of several gull species of the genus Larus around the world. Most of the reports are from the Northern Hemisphere (70%), particularly from Europe and North America. The elements Cd, Hg, Mn, Pb, and Se are the most studied (54%), among which Hg represents about 19%. On the other hand, there is no information for lesser-known trace elements such as Rb, Ti, new technology elements (e.g. Ge, Re, Ta), rare earth elements (e.g. Ce, La, Y), or elements of the platinum group (e.g. Os, Ir, Ru). Even though Larus spp. is a suitable bioindicator of chemical contamination in marine ecosystems, only 28 of the 53 species of the Larus genus have been used on trace elements pollution. Future research should address lesser-known elements which are increasingly used by new technologies.
Keywords: larus; seabirds; gull; trace elements; bioindicators; marine pollution